DOI: 10.26686/wgtn.17067818.v1
|View full text |Cite
|
Sign up to set email alerts
|

Economics and accounting teachers’ beliefs about school-based assessment, the summative and formative tension: A mixed method study

Abstract: <p>The National Certificate of Educational Achievement (NCEA) is New Zealand’s main national qualification for senior secondary school students. A key feature of NCEA is that it allows for more than half of students’ final NCEA grades to be assessed by teachers during the school year through school-based assessment, known as internal assessment. This key role of teachers in awarding qualifications is likely to have an impact on their conceptions of assessment, conceptions of assessment that are not nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 118 publications
(317 reference statements)
0
2
0
Order By: Relevance
“…As highlighted by Thorpe (2017) in relation to assessing group composition, the high-trust foundation, internal assessment components, and inherent flexibility of NCEA allowed teachers to customize their assessments to their curriculum choices. Absent from this study, is any mention of limitations associated with NCEA such as restricting topic choices (Wood & Sheehan, 2020;Yates, 2018). In a survey question about NCEA in both the case studies and the survey, teachers reported NCEA did not limit their curriculum choices negatively.…”
Section: Autonomymentioning
confidence: 97%
See 1 more Smart Citation
“…As highlighted by Thorpe (2017) in relation to assessing group composition, the high-trust foundation, internal assessment components, and inherent flexibility of NCEA allowed teachers to customize their assessments to their curriculum choices. Absent from this study, is any mention of limitations associated with NCEA such as restricting topic choices (Wood & Sheehan, 2020;Yates, 2018). In a survey question about NCEA in both the case studies and the survey, teachers reported NCEA did not limit their curriculum choices negatively.…”
Section: Autonomymentioning
confidence: 97%
“…Writing nearly a decade ago, Burnard's quote seems to reflect the general theme of the international literature to date where the autonomy of teachers is being challenged or eroded (Alexander, 2021;Vangrieken et al, 2017;Yates, 2018). The literature seems to define autonomy broadly as:…”
Section: Teacher Autonomy and The Curriculummentioning
confidence: 99%